Predictors of medication adherence in patients with schizophrenia and bipolar disorder. (17th August 2012) - Jónsdóttir, H.; Opjordsmoen, S.; Birkenaes, A. B.; Simonsen, C.; Engh, J. A.; Ringen, P. A.; Vaskinn, A.; Friis, S.; Sundet, K.; Andreassen, O. A.
<x xml:space="preserve">Abstract</x> Objective: To investigate potential risk factors for medication non‐adherence in patients with schizophrenia and bipolar disorder. Method: A total of 255 patients underwent clinical assessments, neurocognitive testing and blood sampling. The patients were divided into groups of 'No', 'Partial' or 'Full' adherence. Relationships to different risk factors were analyzed. Results: In schizophrenia, use of illicit substances, alcohol and poor insight were related to worse adherence. Schizophrenia patients with No adherence did better on tests of executive functioning, verbal learning and memory and had higher IQ than patients with better adherence. There were higher levels of autonomic side effects in the non‐adherence group, but body mass index was lower in the Partial adherence group than in the Full adherence group. In the bipolar disorder patients, there was an association between the use of illicit substances and alcohol and poor adherence. We found no relationship between adherence behavior and neurocognition in the bipolar disorder group. Conclusion: Substance use is an important risk factor for non‐adherence in patients with schizophrenia and bipolar disorder. Poor insight is also a risk factor in schizophrenia. The results suggest that cognitive dysfunction is not a risk factor for non‐adherence in these diagnostic groups.